No Difference Between Posterolateral Corner Repair and Reconstruction With Concurrent ACL Surgery: Results From a Prospective Multicenter Cohort. Issue 7 (29th July 2019) - Westermann, Robert W.; Marx, Robert G.; Spindler, Kurt P.; Huston, Laura J.; Amendola, Annunziato; Andrish, Jack T.; Brophy, Robert H.; Dunn, Warren R.; Flanigan, David C.; Jones, Morgan H.; Kaeding, Christopher C.; et al.
Background: Injuries to the posterolateral corner (PLC) may occur concurrently with anterior cruciate ligament (ACL) injury. Purpose/Hypothesis: This study evaluated the outcomes of patients who underwent operative management of PLC injuries concurrently with ACL reconstruction in a prospective multicenter cohort. We hypothesized that there would be no differences in outcomes between patients who were treated with PLC repair and PLC reconstruction. Study Design: Cohort study; Level of evidence, 3. Methods: Patients undergoing ACL reconstruction were enrolled into a prospective longitudinal multicenter cohort between 2002 and 2008. Those with complete 6-year follow-up data (patient-reported outcomes and subsequent surgery information) were identified. Excluded from the study were patients with posterior cruciate ligament injuries. Patients who underwent PLC repair were compared with those who underwent PLC reconstruction with regard to interval from injury to surgery, need for revision surgery, and long-term outcomes at 6 years. Results: During the identified time frame, 3026 identified patients underwent primary ACL reconstruction; 34 (1.1%) also underwent concurrent PLC surgery (15 repairs, 19 reconstructions [18 allografts, 1 autograft]). With the numbers available, we did not detect significant differences between groups regarding the rate of meniscal or chondral injuries. Median time to PLC reconstruction was 121 days as compared with 19 days for concurrent ACL reconstruction and PLC repair ( P = .01). There were no between-group differences in Marx activity scores prior to surgery ( P = .4). At 6-year follow-up, there were no between-group differences in Knee injury and Osteoarthritis Outcome Score ( P = .36-.83) or International Knee Documentation Committee score ( P = .84); however, patients treated with PLC reconstructions had lower Marx activity scores (4.1 vs 9.4; P = .02). There was 1 ACL revision in the PLC reconstruction group, and 1 of the PLC repairs was revised to a reconstruction during the follow-up period. Conclusion: Good outcomes were achieved at 6-year follow-up with both repair and reconstruction of PLC injuries treated concurrently with ACL reconstruction. The PLC reconstruction group had lower activity levels 6 years after surgery. The present data suggest that, for appropriately selected patients undergoing acute surgical treatment of combined ACL and PLC injuries, PCL repair can achieve good long-term outcomes.